(untitled) - Dimancescu, Dan (Cambridge, Mass., 1986)
This book important beyond its skillful understanding of the alliances themselves, this work probes the underlying forces and the changing nature of business in a world where knowlegge, as an asset, has surged in importance relative to the more traditional view of fiscal or physical assets.
Keywords: Nghiên cứu công nghiệp,Research, industrial; Hoa Kỳ,United States